Seasonal dynamics of aerobic anoxygenic phototrophs in freshwater lake Vlkov - Kolářová, Eva; Medová, Hana; Piwosz, Kasia; Koblížek, Michal (Folia microbiologica, 2019)
Aerobic anoxygenic phototrophic (AAP) bacteria are a common component of freshwater microbial communities. They harvest light energy using bacteriochlorophyll a-containing reaction centers to supplement their predominantly heterotrophic metabolism. We used epifluorescence microscopy, HPLC, and infrared fluorometry to examine the dynamics of AAP bacteria in the mesotrophic lake Vlkov during the seasonal cycle. The mortality of AAP bacteria was estimated from diel changes of bacteriochlorophyll a fluorescence. The AAP abundance correlated with water temperature and DOC concentration. Its maximum was registered during late summer, when AAP bacteria made up 20% of total bacteria. The novel element of this study is the seasonal measurements of AAP mortality rates. The rates ranged between 1.15 and 4.56 per day with the maxima registered in early summer coinciding with the peak of primary production, which documents that AAP bacteria are a highly active component of freshwater microbial loop.
Keywords: Biodiversity; Phototrophic Processes; aerobní bakterie; světlo; biodiverzita; Oxygen; Bacteria, Aerobic; kyslík; fototrofní procesy; Light; roční období; Seasons; jezera; Lakes